Підвищення довговічності трибоспряжень застосуванням полімерних композиційних матеріалів - Аулін, Віктор Васильович; Aulin, Viktor; Гриньків, Андрій Вікторович; Hrynkiv, Andrii; Деркач, Олексій Дмитрович; Derkach, Oleksii; Макаренко, Дмитро Олександрович; Makarenko, Dmytro; Муранов, Евген Сергійович; Muranov, Evhen; Крутоус, Дмитро Ігорович; Krutous, Dmytro (My University, 2022)
Розглянуто зміни геометричних розмірів деталей посівної секції під дією навантажень в процесі експлуатації. Визначення навантаження, що діють у трибоспряженнях посівної секції. Обґрунтовано математичну модель визначення радіальних, кутових зміщень та величини деформацій. Експериментальними дослідженнями встановлено, що швидкість зношування (0,003 г/год) деталей з ПКМ має лінійну залежність від напрацювання, що дозволяє спрогнозувати ресурс трибоспряжень. The purpose of the work is the theoretical substantiation of the operating modes of the parts of a typical parallelogram mechanism, the determination of the magnitude of the initial deformations and the optimal operating modes of the parts made of polymer-composite materials. Changes in the geometric dimensions of parts of the sowing section under the influence of loads during operation are considered. Determination of the load acting in the tribo couplings of the sowing section of the "Turbosem II 19-60" complex. The mathematical model for determining radial, angular displacements and the magnitude of deformations due to design features and loads on movable couplings is substantiated. The methodology for determining the maximum and minimum compensation of installation deformations for parts made of polymer-composite materials is proposed. Experimental studies have established that the rate of wear (0.003 g/h) of PCM parts has a linear dependence on working life, which allows predicting the resource of tribo couplers. Taking into account the geometric dimensions of the PCM part and the limit value of the gap in the tribo-coupling, it is possible to determine the resource of the moving tribo-coupling with high probability. The obtained linear function of the dependence of the amount of wear on the working life is valid for the material UPA-6-30, under the condition of a linear sliding speed of up to 0.1 m/s and a load on the tribo coupler up to 600 N. Experimental studies have determined the optimal values of the load value - 250 N and the gap - 300 μm in the tribo coupling "polymer composite - steel". The obtained results can be used in the modernization of existing or development of new designs of sowing sections.
Increasing the Durability of Tribocouplers Using Polymer Composite Materials
Keywords: підвищення довговічності; increase in durability; трибоспряження; tribo coupling; установочні деформації; set deformations; полімерно-композиційні матеріали; polymer-composite materials; величина зноcу; amount of wear